Enhancing the Chemical Stability of MXene Through Synergy of Hydrogen Bond and Coordination Bond in Aqueous Solution. Issue 4 (19th February 2023) - Wang, Xiao‐Yun; Liao, Si‐Yuan; Huang, Hai‐Peng; Wang, Qiao‐Feng; Shi, Yu‐Ying; Zhu, Peng‐Li; Hu, You‐Gen; Sun, Rong; Wan, Yan‐Jun
Abstract: MXenes with unique physicochemical properties have shown substantial potential in electromagnetic interference (EMI) shielding. However, the chemical instability and mechanical fragility of MXenes has become a major hurdle for their application. Abundant strategies have been dedicated to improving the oxidation stability of colloidal solution or mechanical properties of films, which always come at the expense of electrical conductivity and chemical compatibility. Here, hydrogen bond (H‐bond) and coordination bond are employed to achieve chemical and colloidal stability of MXenes (0.1 mg mL −1 ) by occupying the reaction sites of Ti3 C2 T x attacking of water and oxygen molecules. Compared to the Ti3 C2 T x, the Ti3 C2 T x modified with alanine via H‐bond shows significantly improved oxidation stability (at room temperature over 35 days), while the Ti3 C2 T x modified with cysteine by synergy of H‐bond and coordination bond can be maintained even after 120 days. Simulation and experimental results verify the formation of H‐bond and Ti‐S bond by a Lewis acid‐base interaction between Ti3 C2 T x and cysteine. Furthermore, the synergy strategy significantly improves the mechanical strength of the assembled film (up to 78.1 ± 7.9 MPa), corresponding the increment of 203% compared to untreated one, almost without compromising the electrical conductivity and EMI shielding performance. Abstract : MXene is easily oxidized and difficult to store in aqueous solution. Cysteine molecules can effectively inhibit the oxidation of Ti3 C2 Tx, which can be attributed to the synergy of the Ti–S bond and H‐bond to promote a stronger interaction between MXene and cysteine, thus to occupy the reactive sites against water molecules attack and thereby to inhibit the oxidation of MXene.